PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS CANVA MATERI PERANGKAT KERAS SEBAGAI BAHAN AJAR GURU MATA PELAJARAN INFORMATIKA PADA KELAS VII SMP MUHAMMADIYAH 8 KEBAKKRAMAT - Kicky Zandov; Siti Supeni; daryono daryono (UNIVERSITAS SLAMET RIYADI, 2023)
The purpose of this study was to produce Canva video-based learning media as teaching materials for informatics teachers in the introduction of hardware and to determine the feasibility of learning media. Researchers use research and development procedures with the Research and Development development method or often also called R&D. In this development stage, to be able to produce Canva-based learning media products that will be developed, the researcher uses the Borg and Gall research and development procedure which has been modified by Sugiyono and is only limited to seven research and development steps, namely potentials and problems, gathering information, product design, design validation, design improvement, product response or testing and product revision. Based on the feasibility assessment of Canva video-based learning media as teaching material for teachers on the imposition of hardware in informatics subjects, informatics according to the assessment of material experts obtained a percentage of 93% in the Very Feasible category, in the Feasibility aspect of presentation it obtained a percentage of 95% in the category very suitable for use, in the feasibility aspect obtained a percentage of 100% in the Very Feasible category. Based on the percentage score, the assessment obtained an average of 94.54% with the category Very suitable for use. These results show that the Canva-based learning media product that has been developed is suitable for use as teacher teaching material and has been tested. media experts get a percentage of 86.6% in the category Very Appropriate to Use, in the Audio and Visual Communication Aspects get a percentage of 80% in the category Worth using. Based on the percentage score, the assessment obtained an average of 82% with the category Very suitable for use. These results show that the Canva-based learning media product that has been developed is suitable for use as teacher teaching material and has been tested.